2018
DOI: 10.5923/j.ijme.20180801.03
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Eucalyptus umbra Wood for Timber Structures

Abstract: This study involved the study of physical and mechanical properties of Eucalyptus umbra wood for its use in timber structures. Two physical and fourteen mechanical properties tests were performed according to Brazilian code ABNT NBR 7190:1997. Two moisture contents were considered: above the Fiber Saturation Point (30%) and standardized point 12%. Decreasing the moisture content, this study presented an increase in eight mechanical properties. Oppositely, five mechanical properties presented decreasing of valu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…The measured compressive strength ranged from 2.6 to 5.6 MPa, with an average of 4.2 MPa. These results are comparable with similar values reported in the literature for the same species (McKimm 1985) and for other species of the same Eucalyptus genus (Nogueira et al 2018a). On the other hand, the values measured in this study were similar to those reported by Lobão et al (2004) for Eucalyptus grandis (4.9 MPa), and the results obtained by Awan et al (2012) for Eucalyptus camaldulensis (5.5 MPa).…”
Section: Resultssupporting
confidence: 92%
“…The measured compressive strength ranged from 2.6 to 5.6 MPa, with an average of 4.2 MPa. These results are comparable with similar values reported in the literature for the same species (McKimm 1985) and for other species of the same Eucalyptus genus (Nogueira et al 2018a). On the other hand, the values measured in this study were similar to those reported by Lobão et al (2004) for Eucalyptus grandis (4.9 MPa), and the results obtained by Awan et al (2012) for Eucalyptus camaldulensis (5.5 MPa).…”
Section: Resultssupporting
confidence: 92%
“…Similarly to Lahr et al [28] and Nogueira et al [29] studies, the samples used in these sixteen tests were prepared and conditioned for stabilization in both moistures at green (30%) and standard point (12%) in the Laboratory of Wood and Timber Structures (LaMEM) at the School of Engineering of São Carlos from the University of São Paulo (USP-EESC), São Carlos, Brazil. Furthermore, 310 determinations (or repetitions) were carried out in the aforementioned sixteen physical-mechanical parameters for the evaluation of Eucalyptus maidenii.…”
Section: Methodsmentioning
confidence: 99%